Case presentation and management of Lyme disease patients: a 9-year retrospective analysis in France - Perthame, Emeline; Chartier, Loïc; George, Jean-Claude; Varloud, Marie; Ferquel, Elisabeth; Choumet, Valérie (Frontiers in Medicine, 2024)
Lyme borreliosis (LB) is the most common vector disease in temperate countries of the northern hemisphere. It is caused by Borrelia burgdorferi sensu lato complex. To study the case presentation of LB in France, we contacted about 700 physicians every year between 2003 and 2011. An anonymous questionnaire was established allowing the collection of 3,509 cases. The information collected was imported or directly entered into databases and allowed identifying variables that were validated in a multiple correspondence analysis (MCA). Sixty percent of the cases were confirmed, 10% were probable, 13.5% doubtful, 10.2% asymptomatic seropositive and 6.3% were negative. The clinical manifestations reported were cutaneous (63%), neurological (26%), articular (7%), ocular (1.9%) and cardiac (1.3%). Almost all patients were treated. When focusing more particularly on confirmed cases, our studies confirm that children have a distinct clinical presentation from adults. There is a gender effect on clinical presentation, with females presenting more often with erythema migrans or acrodermatitis chronica atrophicans than males, while males present more often with neurological signs or arthritis than females. In conclusion, it is the first time that a comprehensive study of suspected Lyme borreliosis cases has been conducted over several years in France. Although we were not able to follow the clinical course of patients after treatment, these results suggest the interest of refining the questionnaire and of following up a cohort of patients over a sufficiently long period to obtain more information on their fate according to different parameters.